Effect of Rosa laevigata on PM10-Induced Inflammatory Response of Human Lung Epithelial Cells. (7th September 2020) - Ko, Hyun Min; Choi, Seung-Han; Kim, Yumi; An, Eun-Jin; Lee, Seung-Hyeon; Kim, Kwanil; Jung, Hee-Jae; Jang, Hyeung-Jin
Abstract : Particulate matter 10 (PM10) with a diameter of less than 10 mm causes inflammation and allergic reactions in the airways and lungs, which adversely affects asthmatic patients. In this study, we examined the anti-inflammatory effects of Rosa laevigata (RL), which has been previously investigated medicinally in Korea and China for the discovery of plant-derived anti-inflammatory agents with low side effects, using a PM10-induced lung inflammatory disease model. Using MTT assay, we confirmed that in A549 cells pretreated with RL, cytotoxicity induced by PM10 (100  μ g/mL) exposure was attenuated. In addition, western blotting revealed that RL suppressed the expression level of MAPK/NF- κ B pathways and its downstream signal, COX-2 in PM10-induced A549 cells. Moreover, real-time PCR demonstrated that RL downregulated the mRNA expression level of inflammatory cytokines (TNF- α, IL-1 β, IL-6, IL-13, and IL-17) in PM10-induced A549 cells. Based on the results of this study, RL has been shown to relieve inflammation in the lungs due to PM10 exposure. Therefore, RL may be developed as a natural remedy for respiratory diseases caused by PM10 exposure.